Strategy implementation versus middle management self‐interest - Guth, William D.; Macmillan, Ian C. (Strategic Management Journal, 1986)
Abstract This paper focuses on middle management motivation to implement strategy. It uses expectancy theory to predict that middle managers will intervene in organizational decision‐making processes leading to strategy implementation when their self‐interest is at stake. It develops the notion of ‘counter effort’, as an extension of expectancy theory. The paper reports an empirical study of middle management intervention theory. The data and analysis of this study provide strong, if indirect, evidence that middle managers who believe that their self‐interest is being compromised can not only redirect a strategy, delay its implementation or reduce the quality of its implementation, but can also even totally sabotage the strategy. Implications of the study for the management of strategy implementation are developed.